Question

using the derivative definition how do I find f(x) = -6(square root over x).

Expert Answer

1 Rating

Want to see the step-by-step answer?

See Answer

Check out a sample Q&A here.

Want to see this answer and more?

Experts are waiting 24/7 to provide step-by-step solutions in as fast as 30 minutes!*

See Answer
*Response times vary by subject and question complexity. Median response time is 34 minutes and may be longer for new subjects.
Tagged in
MathCalculus

Derivative

Related Calculus Q&A

Find answers to questions asked by student like you

Q: Suppose that the revenue function for a certain product is given by  R(x)= 15(2x+1)^-1 + 30x-15 wher...

A: We have to find (a) The marginal revenue when 2000 units are sold.(b) How is revenue changing when 2...

Q: Determine the following indefinite integral. 324 dx, x> In 18 A dx 324- e2x Type an exact answer. Us...

A: The given integral is,

Q: 4. Two stationary patrol cars equipped with radar are 6 miles apart on a highway. A truck passes a p...

A: Using Mean value theoremt,to calculate the speed limit of the truck driver passing the second patrol...

Q: Find the intervals on which f is increasing and the intervals on which it is decreasing   f(x) = -2 ...

A: First, we find f'(x).

Q: Determine if y=e−x+8x−9 is a solution to the initial value problem given by y′+1=8x−y and y(0)=−8.

A: The given differential equation is y′+1=8x−y.The solution of the deferential equation is given as, y...

Q: Is y=e6x −3x−2 a solution to the differential equation shown below? y′−6y=7x+3

A: Here given differential equation is:Find the solution of given differential equation and match the g...

Q: If f(x) 3x-2then f(x) = x 2x+ 2x5/3 2x 2x-1 12 1+5x8/3 3x2 2x-53-3x-3/2 x2 none of the above

A: The given function is,

Q: Use properties of limits and algebraic methods to find the limit, if it exists. (If the limit is inf...

A: f(x) = 12 − 2x   if x < 2 and x2 − x   if x ≥ 2We have to find lim x→2 f(x)

Q: Calculus Question

A: Let's call the given integral as I. Further let's make the substitution: x2 + 1 = zHence, 2xdx = dzP...